(untitled) (Informatica, 2024)
Due to the advancement of science and technology, the application of virtual reality technology is more and more extensive, and people can truly immerse themselves in virtual space through virtual reality. Relying on the visual VR reconstruction algorithm, this paper deals with the problems of "burring" and insufficient compression of relatively simple video imaging devices. Based on the virtual reality technology, the multimedia effect of the video image is processed, and according to six operation modules, a system combining virtual reality technology is designed. From the aspect of determining the relationship between video image data and color, it is classified into three types: binary image, pseudo-color image, and grayscale image, and the grid of each point is defined and quantified. The extreme value filtering algorithm performs a sorting calculation on the image pixels in the filtering window to improve the image effect with the threshold value suitable for filtering processing. Simulation results show that the VR visual restoration algorithm has a higher compression ratio and visual efficiency and can effectively support multimedia VR image improvement and simulation analysis